2018
DOI: 10.1016/j.neuropsychologia.2018.07.031
|View full text |Cite
|
Sign up to set email alerts
|

Recognition memory shielded from semantic but not perceptual interference in normal aging

Abstract: Normal aging impairs long-term declarative memory, and evidence suggests that this impairment may be driven partly by structural or functional changes in the medial temporal lobe (MTL). Theories of MTL memory function therefore make predictions for age-related memory loss. One theory - the Representational-Hierarchical account - makes two specific predictions. First, recognition memory performance in older participants should be impaired by feature-level interference, in which studied items contain many shared… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 102 publications
4
9
0
Order By: Relevance
“…Thus, they found that in this task age-related memory errors were driven more by perceptual than semantic relatedness. The results converge with those of another study that used intermixed visual word lists without distinctive fonts: Wilson, Potter, & Cowell (2018) also found no significant agerelated increase in false recognition of critical DRM lures, although memory was measured solely in terms of discrimination between studied items and lures (as in Fraundorf, Hourihan, Peters, & Benjamin, 2019).…”
Section: Introductionsupporting
confidence: 87%
See 4 more Smart Citations
“…Thus, they found that in this task age-related memory errors were driven more by perceptual than semantic relatedness. The results converge with those of another study that used intermixed visual word lists without distinctive fonts: Wilson, Potter, & Cowell (2018) also found no significant agerelated increase in false recognition of critical DRM lures, although memory was measured solely in terms of discrimination between studied items and lures (as in Fraundorf, Hourihan, Peters, & Benjamin, 2019).…”
Section: Introductionsupporting
confidence: 87%
“…We made two sets of alternative predictions. If Tun et al (1998) were correct that older people are more prone to gist memory than young adults when word lists are blocked, an age effect on false recognition would now be observed, unlike in both Burnside et al's (2017) experiments and (D. M. Wilson et al, 2018). Alternatively, if associative false recognition is age-invariant when there is no prior recall test, we would find Bayesian evidence in favour of the null hypothesis, like Burnside et al (2017).…”
Section: Introductionmentioning
confidence: 71%
See 3 more Smart Citations